2008
DOI: 10.1177/1524839908318167
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Organizing Approach to Promoting Physical Activity in Older Adults: The Southeast Senior Physical Activity Network

Abstract: This article describes a community organizing approach to promoting physical activity among underserved older adults in southeast Seattle: the Southeast Senior Physical Activity Network (SESPAN). The organizing strategy involves networking with a variety of community-based organizations, with two broad objectives: (a) program objective-to make connections between two (or more) community-based organizations to create senior physical activity programs where none existed before; and (b) coalition objective-to bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…However, after checking the full texts of these studies, 39 of them were excluded since twelve were not PA governmental programs (Aoki et al, 2015;Brach, Nieder, Nieder, & Mechling, 2009;Burton, Lewin, Clemson, & Boldy, 2013;Etkin, Prohaska, Harris, Latham, & Jette, 2006;Filiatrault et al, 2008;Nguyen et al, 2007;Gawler et al, 2016;Liang et al, 2017;Matsudo et al, "Effects of Physical Activity Governmental Programs on Health Status in Independent Older Adults: A Systematic Review" by Valdés-Badilla P et al Journal of Aging andPhysical Activity © 2018 Human Kinetics, Inc. 2003;Quehenberger, Cichocki, & Krajic, 2014;Robitaille et al, 2012;Zgibor et al, 2016), five included participants younger than 60 years old in their samples (Ablah et al, 2015;Cameron, Chahine, Selig, & Newton, 2008;Hetherington et al, 2015;Martinson et al, 2010;Wilcox, Dowda, Wegley, & Ory, 2009), nine did not respond to the object of study of the present review (Babazono, Kuwabara, Hagiihara, Nagano, & Ishihara, 2011;Cheadle, Egger, LoGerfo, Walwick, & Schwartz, 2010a;Dangour et al, 2007;Filiatrault et al, 2007;Goodman, Davies, Tai, Dinan, & Iliffe, 2007;Griffin et al, 2010;Hayashi, Kondo, Suzuki, Yamada, & Matsumoto, 2014;Kanamori et al, 2012;Stewart et al, 2006), six just collected results from only one assessment (post-evaluation) of the participants (Benedetti, Schwingel, Gomez, & Chodzko-Zajko, 2012;Cheadle, Egger, LoGerfo, Schwartz, & Harris, 2010b;da Fonte et al, 2016;Figueira et al, 2009;Valdés-Badilla et al, 2017;…”
Section: Study Selection Eligibility Criteria and Data Extractionmentioning
confidence: 99%
“…However, after checking the full texts of these studies, 39 of them were excluded since twelve were not PA governmental programs (Aoki et al, 2015;Brach, Nieder, Nieder, & Mechling, 2009;Burton, Lewin, Clemson, & Boldy, 2013;Etkin, Prohaska, Harris, Latham, & Jette, 2006;Filiatrault et al, 2008;Nguyen et al, 2007;Gawler et al, 2016;Liang et al, 2017;Matsudo et al, "Effects of Physical Activity Governmental Programs on Health Status in Independent Older Adults: A Systematic Review" by Valdés-Badilla P et al Journal of Aging andPhysical Activity © 2018 Human Kinetics, Inc. 2003;Quehenberger, Cichocki, & Krajic, 2014;Robitaille et al, 2012;Zgibor et al, 2016), five included participants younger than 60 years old in their samples (Ablah et al, 2015;Cameron, Chahine, Selig, & Newton, 2008;Hetherington et al, 2015;Martinson et al, 2010;Wilcox, Dowda, Wegley, & Ory, 2009), nine did not respond to the object of study of the present review (Babazono, Kuwabara, Hagiihara, Nagano, & Ishihara, 2011;Cheadle, Egger, LoGerfo, Walwick, & Schwartz, 2010a;Dangour et al, 2007;Filiatrault et al, 2007;Goodman, Davies, Tai, Dinan, & Iliffe, 2007;Griffin et al, 2010;Hayashi, Kondo, Suzuki, Yamada, & Matsumoto, 2014;Kanamori et al, 2012;Stewart et al, 2006), six just collected results from only one assessment (post-evaluation) of the participants (Benedetti, Schwingel, Gomez, & Chodzko-Zajko, 2012;Cheadle, Egger, LoGerfo, Schwartz, & Harris, 2010b;da Fonte et al, 2016;Figueira et al, 2009;Valdés-Badilla et al, 2017;…”
Section: Study Selection Eligibility Criteria and Data Extractionmentioning
confidence: 99%
“…These evaluations that document intermediate community change outcomes were sometimes accompanied by population‐level surveys and/or strategy specific outcome evaluations (Cheadle, Egger, LoGerfo, Walwick, & Schwartz, ). In the current review, these often were mentioned in a description of the larger evaluation, but results were not presented alongside the intermediate community change outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Older adults are the most sedentary segment of our population (CDC, 2016a). A number of randomized control trials have been tested and reported to be effective in improving physical activity levels among older adults; however, few have been adopted in community-based settings (Cheadle, Egger, LoGerfo, Walwick, & Schwartz, 2010; Wilcox et al, 2006). To combat the widespread problem of physical inactivity and to benefit large masses and improve human health, it is essential to extend evidence-based findings from clinical trials into community-based settings and to the population that is more representative.…”
Section: Discussionmentioning
confidence: 99%